2020
DOI: 10.1186/s12909-020-1965-4
|View full text |Cite
|
Sign up to set email alerts
|

Forum theater staging of difficult encounters with patients to increase empathy in students: evaluation of efficacy at The University of Angers Medical School

Abstract: Background: Physician empathy has been associated with improved clinical outcomes and lower physician burnout. We evaluated whether forum theater (FT), a form of applied drama that allows participants to enter the performance and represent the actions associated with emotions, would foster empathy in medical students, and which underlying variables would be associated to empathy scores. Methods: Three classes totaling 488 fourth-year medical students participated in the study. Forum theater was used to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
1
23
0
1
Order By: Relevance
“…Additionally, the participants in FP workshops had experienced more often that they were able to act according to their own moral beliefs. Our results are consistent with research confirming that role-playing is an effective way to enhance empathy and to improve the communication skills of health professionals [ 29 , 30 ]. They also support the findings that showed that participants in FP workshops had experienced a change in their motivation and perceived ability to act in situations of AHC [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the participants in FP workshops had experienced more often that they were able to act according to their own moral beliefs. Our results are consistent with research confirming that role-playing is an effective way to enhance empathy and to improve the communication skills of health professionals [ 29 , 30 ]. They also support the findings that showed that participants in FP workshops had experienced a change in their motivation and perceived ability to act in situations of AHC [ 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our 1 point gain for five items matches the 4 points gain out of 20 items (4/20) which were observed in 488 French medical students trained via forum theatre and tested after the training sessions. 39 Using another communication skill training in India, D'Souza showed that a single training session transiently but significantly improved the JSPE score by 4.5/20. 34 One of the main concerns for both adaptation 87 and readaptation 75 programs is the duration of the effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is important in order to improve the patient-caregiver relationship as well as to achieve better adherence to treatment and better health outcomes. 7,18 A variety of interventions have taken this need into account: visiting patients at home, 19,20 writing about the patient's point of view, 21 student inpatient hospitalization, 22 mindfulness skills training, 23,24 communication skills training, [25][26][27][28][29][30][31][32][33][34] simulated experiential learning, 35,36 perspective taking training, 37,38 theater improvisation teaching, 39 role playing, 40,41 and Balìnt group training. 42,43 In the following paragraph, we shall see that several intervention types are likely to increase empathy skills among medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Several educational principles underlie our initiative. Our workshops were inspired by the well‐studied concept of forum theatre—which embraces experience sharing to foster connection 12 —in that group debrief and verbal self‐reflections strategically follow each exercise. Participants are encouraged to share difficult interpersonal and interprofessional encounters they have experienced and brainstorm how they might implement the workshop tools in their clinical practice when navigating future challenging patient encounters.…”
Section: Approachmentioning
confidence: 99%